EFEKTIVITAS EDUKASI VIDEO DALAM KELENGKAPAN PENJELASAN CARA PENGGUNAAN MDI DENGAN/TANPA SPACER PADA MAHASISWA FARMASI - Amelia Lorensia; Rifaatul Laila Mahmudah; asri dewayani; Nevyta Fitriandasari (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
Asthma is a chronic disease that can be prevented by treatment with reliever. Metered Dose Inhalers (MDI) is one of the rapid treatments for asthma, but the use of MDI techniques is still lacking in patients can cause asthma treatment is not optimal. Pharmacy students are the seeds of advanced study programs, namely pharmacists who will be responsible for explaining to patients about how to use MDI and MDI with spacers correctly. This study aims to determine the effect of providing education in the form of videos on how to use inhalers. This study was a quasi experimental study using a checklist. Sampling using the non random sampling method using purposive techniques. Data will be processed with descriptive statistical analysis. The MDI group research samples were 85 subjects while the MDI group with 84 spacers. The results of the study showed that there were differences in the completeness of the explanation on how to use MDI (p = 0,000) and MDI with spacers (p = 0,000) after giving video education. So it can be concluded that video education is effective in increasing the completeness of the explanation on how to use MDI and MDI with spacers.